Non-Muslims in The Nation-State: The Medina Charter as a Prototype for Islamic Wasathiyah Implementation in Indonesia - Alwi, Zulfahmi (Ihyaussunnah : Journal of Ulumul Hadith and Living Sunnah, 2022)
In recent years, rampant intolerant cases have damaged Indonesia's religious image in various forms and waned national commitment. Starting with the refusal of non-Muslims to live in certain areas and the rejection of the establishment of houses of worship for certain religions, it is clear that religious freedom in Indonesia requires serious attention in order to implement wasathiyah values in Indonesia. This paper seeks to provide an understanding of non-Muslims in the nation-state, the Medina Charter as the Prophet's political strategy in realizing national commitment to become a model for the implementation of wasathiyah values ​​in Indonesia. This paper uses a qualitative approach with data collection techniques through a literature study. The results of this study indicate that at least it can be understood that when the Prophet initiated the Medina Charter as a political policy and strategy in realizing national commitment, it could be used as a model for implementing wasathiyah values ​​in Indonesia. The substance of the Medina Charter guarantees the social, political, religious, and cultural rights of the community to realize the unity and integrity of the nation, which is part of the national commitment that must be maintained and cared for properly. In addition, the values ​​contained in the Medina Charter are the values ​​taught in Islam and are in line with the spirit of national commitment in Indonesia. Therefore, the results of this research hopefully can contribute to rebuilding the spirit of togetherness and diversity in the Unitary Republic of Indonesia (NKRI)